Bioaccumulation and biochemical markers in feral crab (carcinus maenas) exposed to moderate environmental contamination: the impact of non-contamination-related variables - Pereira, P.
Moderate contamination is a challenging scenario for ecotoxicologists because of the occurrence of subtle biomarker responses and the increased relevance of non-contamination related variables. This investigative biomonitoring study was performed in a moderately contaminated coastal system (Óbidos lagoon, Portugal) to examine winter–summer variations on biochemical responses and accumulated metals in Carcinus maenas , searching for associations with environmental and biological factors. Males and females were collected in three sites: Barrosa (BB) and Bom-Sucesso (BS) in upper lagoon, and the middle lagoon (ML), closer to the lagoon inlet. Water and sediment were monitored for metals (Cu, Mn, Ni, Cr, Cd). Catalase (CAT), glutathione peroxidase (GPx), glutathione S -transferase (GST), total glutathione content (GSH t ), lipid peroxidation (LPO), and ethoxyresorufin- O -deethylase (EROD), as well as Cu, Mn, Ni, Cr and Cd were measured in the crabs’ hepatopancreas. Inter-site differences, though infrequent, pointed to the presence of crab stressors at BB. This was particularly obvious in summer when higher GSTas well as lower GSH t and EROD were found in females, and accompanied by higher Ni accumulation. Seasonal differences of biochemical responses superimposed spatial variations in line with the contrasting winter–summer conditions regarding water quality and, to a lesser extent, with metal bioaccumulation. CAT, GSH t , and LPO were higher in summer, whereas enhancements of GPx and GSTwere recorded in winter. Winter increases were in agreement with higher availability of metals in water and enhancement of accumulated levels, particularly in females as emphasized by a bioaccumulation index. On the other hand, increases in summer were mainly driven by non-contamination related factors. Males and females exhibited different patterns of metal accumulation and biochemical responses, with females being more responsive, as confirmed by a general stress index (IBR). Results recommend gender separation in biomonitoring programs using crabs. The integration of biochemical responses into IBR substantiated data interpretation. This is particularly relevant under moderate contamination allowing for better site-distinction rather than biochemical responses considered individually.